Gene therapy – are we ready now?. (6th May 2022) - Kaczmarek, Radoslaw
Abstract: Introduction: Haemophilia therapy has evolved from rudimentary transfusion‐based approaches to an unprecedented level of innovation with glimmers of functional cure brought by gene therapy. After decades of misfires, gene therapy has normalized factor (F)VIII and factor (F)IX levels in some individuals in the long term. Several clinical programmes testing adeno‐associated viral (AAV) vector gene therapy are approaching completion with imminent regulatory approvals. Discussion: Phase 3 studies along with multiyear follow‐up in earlier phase investigations raised questions about efficacy as well as short‐ and long‐term safety, prompting a reappraisal of AAV vector gene therapy. Liver toxicities, albeit mostly low‐grade, occur in the first year in at least some individuals in all haemophilia A and B trials and are poorly understood. Extreme variability and unpredictability of outcome, as well as a slow decline in factor expression (seemingly unique to FVIII gene therapy), are vexing because immune responses to AAV vectors preclude repeat dosing, which could increase suboptimal or restore declining expression, while overexpression may result in phenotoxicity. The long‐term safety will need lifelong monitoring because AAV vectors, contrary to conventional wisdom, integrate into chromosomes at the rate that calls for vigilance. Conclusions: AAV transduction and transgene expression engage the host immune system, cellular DNA processing, transcription and translation machineries in ways that have been only cursorily studied in the clinic. Delineating those mechanisms will be key to finding mitigants and solutions to the remaining problems, and including individuals who cannot avail of gene therapy at this time. Abstract :